Youth hearing impairment: Early detection is key. Issue 4 (April 2017) - Sampson, Janice; Thompson, Heather
Abstract : Timely identification of hearing loss is crucial for ensuring early intervention to allow normal development of language skills and social interactions. Be prepared by updating your knowledge of hearing assessment, screening options, and appropriate interventions for children.